El reforzamiento de las relaciones franco-peruanas en el campo de la diplomacia económica (1945-1975) - Cayo Durand de Geist, Getsiva (2017)
In recent times, the study of international relations began to explore new areas of research and to invent innovative approaches. Scholars turned their attention to the role of “economic diplomacy” as an important mean of foreign policy in fostering economic development and expansion. The case of the franco-peruvian economic diplomacy allows analyzing different structures and strategies which were directed towards a bilateral rapprochement. This paper studies the actors, functions and the institutional framework of the foreign economic policy of France and Peru between 1945 and 1975. In a comparative perspective, it is thereby possible to identify, a part of structural similarities, two clearly contrasting strategies in their economic diplomacy. On the one hand, France invested in the extending and specializing of their diplomatic staff in order to implement an active economic diplomacy. On the other hand, due to political and financial reasons, Peru often remained in a more passive role in the search for foreign investments.